Proceedings of the 38th Annual Hawaii International Conference on System Sciences
DOI: 10.1109/hicss.2005.153
|View full text |Cite
|
Sign up to set email alerts
|

Common Data Model for Design Document Exchange in Business-to-Business Networks

Abstract: Design documents can be exchanged in business-tobusiness networks through Product Data Management (PDM) system integration. This rarely used approach provides new possibilities for faster and more controlled document exchange according to networked product development (PD) needs. PDM system integration requires, however, a common understanding of the exchanged document metadata (e.g. name, type, and version of the document). We analyzed internal data models for design documents in six companies to find their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Scott et al At the level of deployment, there exists even less research, perhaps due to the lack of reports from organizational implementations of ECM in general. However, case studies of experiences from ontology and metadata deployment have been reported (e.g., DiengKuntz et al, 2006;Jokinen et al, 2005).…”
Section: Process Perspectivementioning
confidence: 99%
“…Scott et al At the level of deployment, there exists even less research, perhaps due to the lack of reports from organizational implementations of ECM in general. However, case studies of experiences from ontology and metadata deployment have been reported (e.g., DiengKuntz et al, 2006;Jokinen et al, 2005).…”
Section: Process Perspectivementioning
confidence: 99%
“…This line of inquiry seems relevant for several reasons. First, product development represents a knowledge-intensive, high-value-added strategic activity which is increasingly conducted among geographically-dispersed teams [14]. Second, past research in the specific context of product development remains scarce and the empirical evidence limited (for exceptions, see [38], [29]).…”
Section: Introductionmentioning
confidence: 99%